Cochrane Database of Systematic Reviews 2013
DOI: 10.1002/14651858.cd007654.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of weight-reducing drugs in hypertensive patients

Abstract: In patients with elevated blood pressure, orlistat and sibutramine reduced body weight to a similar degree. In the same trials, orlistat reduced blood pressure and sibutramine increased blood pressure. No trials investigating rimonabant in people with elevated blood pressure could be included. Long-term trials assessing the effect of orlistat, sibutramine and rimonabant on mortality and morbidity are lacking. Rimonabant and sibutramine have been withdrawn from the market for the time being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 73 publications
0
10
0
Order By: Relevance
“…The effect on diastolic tension was not significant in any of the cases. According to what we know in relation to the treatment of hypertension, the effect of diet compared to pharmacological treatment on this parameter is more discreet, and yet, it has great importance in the development of cardiovascular disease [39].…”
Section: Discussionmentioning
confidence: 99%
“…The effect on diastolic tension was not significant in any of the cases. According to what we know in relation to the treatment of hypertension, the effect of diet compared to pharmacological treatment on this parameter is more discreet, and yet, it has great importance in the development of cardiovascular disease [39].…”
Section: Discussionmentioning
confidence: 99%
“…Lin et al (2011) reviewed the literature and reported that dietary counseling and an increase in PA were associated with decreased BMI, blood pressure, and total cholesterol. Siebenhofer et al (2013) determined that weight-reducing diets decreased blood pressure and body weight.…”
Section: Discussionmentioning
confidence: 99%
“…This is considered unlikely by some researchers, however, as the BP-lowering effect occurs earlier than any significant weight loss 52. BP reductions are associated with weight loss, as evidenced in clinical trials and epidemiologic studies5658 in which reductions in systolic BP associated with weight loss in patients with T2DM have been reported 59. The weight loss observed during the first weeks after treatment initiation with an SGLT2 inhibitor is presumed to be mainly due to volume contraction, rather than to the loss of fat and/or lean tissue 54.…”
Section: Sglt2 Inhibitors and Bp Controlmentioning
confidence: 99%